Frequency of neck pain and its associated factors among Post CABG patients - Shahzad, Ambreen; Aijaz Ali, Saba; Yasmeen, Samreen; Sidra tul Muntaha; Hussain, Tajammul; Rehaman, Madiha (International Journal of Endorsing Health Science Research, 2019)
Background: Chronic postoperative pain (CPOP) is a well-recognized problem in Post-Coronary artery bypass grafting (CABG) patients. Post CABG upper extremity pain is found to be common among these patients effecting quality of life and hinders with the routine activities. The aim of this study was to identify the frequency of neck pain and its associated factors among post-operative CABG patients. Methodology: A cross-sectional study was conducted in Dow University of Health Science, Karachi between April 2018 to November 2018. The sample size 78 was calculated by open epi calculator. Both male and female Postoperative CABG patients with a one-year follow-up were selected with or without neck pain aged between 30-75 years from Outpatient Department. Patients below <30 years of age and those with any other surgeries before or any malignant disease were excluded from the study sample. A questionnaire was given to grade their overall experience of pain on Visual Analogue Scale (VAS) and to fill out Neck Disability Index (NDI) for their neck pain. The data was analysed using SPSS version 21 and Chi square T-test was applied to evaluate the significance. Results: Out of 78 patients there were 32 (41%) females and 46 (58%) males with a mean age range between 30-75 years. 51.3% had neck pain presented within 12 hours of onset of symptoms while 48% had no complaint of neck pain. After CABG, 40 (51.2%) patients developed pain in their neck within 1 year of follow up. The mean VAS score was 5.32 out of 10 points on the basis of which 38 patients didn’t experienced any pain while 20 suffered from moderate pain, 12 from severe pain and 8 patients from mild pain. Conclusion: Patients following CABG surgery develop neck pain within one-year follow-up associated with restricted neck and shoulder range of motion. They also experienced muscle tenderness in their trapezius and sternocleidomastoid muscles followed by frequent headaches.